2016
DOI: 10.5194/gmd-9-1937-2016
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Coupled Model Intercomparison Project Phase 6 (CMIP6) experimental design and organization

Abstract: Abstract. By coordinating the design and distribution of global climate model simulations of the past, current, and future climate, the Coupled Model Intercomparison Project (CMIP) has become one of the foundational elements of climate science. However, the need to address an everexpanding range of scientific questions arising from more and more research communities has made it necessary to revise the organization of CMIP. After a long and wide community consultation, a new and more federated structure has bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
6,705
1
30

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 7,628 publications
(6,768 citation statements)
references
References 40 publications
32
6,705
1
30
Order By: Relevance
“…The CMIP6 solar forcing dataset described in this paper and the metadata description have been published at http://solarisheppa.geomar.de/cmip6 and linked to the Earth System Grid Federation (ESGF), https://esgf-node.llnl.gov/projects/ input4mips/, with version control and digital objective identifiers (DOIs) assigned. An overview of the CMIP6 Special Issue can be found in Eyring et al (2016).…”
Section: Solar Ozone Forcingmentioning
confidence: 99%
See 2 more Smart Citations
“…The CMIP6 solar forcing dataset described in this paper and the metadata description have been published at http://solarisheppa.geomar.de/cmip6 and linked to the Earth System Grid Federation (ESGF), https://esgf-node.llnl.gov/projects/ input4mips/, with version control and digital objective identifiers (DOIs) assigned. An overview of the CMIP6 Special Issue can be found in Eyring et al (2016).…”
Section: Solar Ozone Forcingmentioning
confidence: 99%
“…An atmospheric ionization dataset has been calculated based on the Ap-based precipitation model, using a computationally fast ionization parameterization (Fang et al, 2010) and atmospheric composition from the NRLMSISE-00 model (Picone et al, 2002). This calculation considered MEE (30-1000 keV) with maximum energy deposition at altitudes between about 60 and 90 km (van de Kamp et al, 2016).…”
Section: Mid-energy Electrons (Mees) From the Radiation Beltsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new version of the EC-Earth model is currently under development that will use the aerosol number and mass concentrations from TM5 to calculate cloud activation in IFS. This representation will be used for the Aerosol Chemistry Model Intercomparison Project (AerChemMIP; Collins et al, 2017) as part of the WCRP Coupled Model Intercomparison Project phase 6 (CMIP6; Eyring et al, 2016). Although computationally demanding, the inclusion of spectral (bin) microphysics might be necessary to achieve a level of detail necessary to determine the impact of clouds on the characteristics of aerosol size distributions.…”
Section: Resultsmentioning
confidence: 99%
“…An accurate representation of stratospheric ozone in climate models is therefore essential if they are to be used to project realistic future climate behavior (e.g., Nowack et al, 2015). While many climate models calculate stratospheric ozone distributions with a fully coupled stratospheric chemistry scheme, Eyring et al (2016) reported that not all models participating in phase 6 of the Coupled Model Intercomparison Project (CMIP6) will have that ability and therefore need to prescribe atmospheric ozone concentrations. This requires a long-term, latitudinally and vertically resolved ozone database.…”
Section: Introductionmentioning
confidence: 99%